Do individual factors and neighborhood context explain ethnic differences in juvenile delinquency? - Peeples, Faith (Journal of quantitative criminology, 1994)
Individually measured factors and neighborhood context were related to juvenile delinquency in a community sample of 506 urban, public-school boys. Neighborhood context was measured with an objective, census-based score that classified neighborhoods as underclass or not underclass. When African American youths and white youths were compared without regard to neighborhood context, African American youths were more frequently and more seriously delinquent than white youths. When African American youths did not live in underclass neighborhoods, their delinquent behavior was similar to that of the white youths. Hierarchical multiple regression analyses showed that boys' hyperactivity and parental supervision were the strongest correlates of delinquency. Single-parent status and poverty/welfare use were not related to delinquent behavior. Once individually measured factors were accounted for, residence in underclass neighborhoods was significantly related to delinquent behavior while ethnicity was not. This study points to the importance of including the neighborhood context when addressing the social problems of African American youths.